2017
DOI: 10.1016/j.neuron.2017.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Beta Peptides Block New Synapse Assembly by Nogo Receptor-Mediated Inhibition of T-Type Calcium Channels

Abstract: SUMMARY Compelling evidence links amyloid beta (Aβ) peptide accumulation in the brains of Alzheimer’s disease (AD) patients with the emergence of learning and memory deficits; yet a clear understanding of the events that drive this synaptic pathology are lacking. We present evidence that neurons exposed to Aβ are unable to form new synapses, resulting in learning deficits in vivo. We demonstrate the Nogo receptor family (NgR1-3) act as Aβ receptors mediating an inhibition of synapse assembly, plasticity and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…The sizes of the aggregates in the presence of NaCl, are also larger compared to the no salt condition. The aggregate size after 5 h of incubation without salt was~60 nm 3 (Figure 3f), whereas similar sized aggregates were observed within 1 h of incubation in the presence of NaCl (Figure 3c). These results clearly indicate that the presence of NaCl strongly influences the acceleration of aggregation and becomes an important factor allowing aggregates to grow faster.…”
Section: Aggregation On Binary Slb Mixture (Popc:pops)mentioning
confidence: 83%
See 1 more Smart Citation
“…The sizes of the aggregates in the presence of NaCl, are also larger compared to the no salt condition. The aggregate size after 5 h of incubation without salt was~60 nm 3 (Figure 3f), whereas similar sized aggregates were observed within 1 h of incubation in the presence of NaCl (Figure 3c). These results clearly indicate that the presence of NaCl strongly influences the acceleration of aggregation and becomes an important factor allowing aggregates to grow faster.…”
Section: Aggregation On Binary Slb Mixture (Popc:pops)mentioning
confidence: 83%
“…Growing evidence suggests the involvement of protein oligomers in the development of protein misfolding diseases, including Alzheimer's disease (AD) and Parkinson's disease (PD); however, limited knowledge exists regarding the molecular mechanisms behind the aggregation processes for these oligomers [1][2][3][4]. The amyloid cascade hypothesis (ACH), proposed more than a quarter-century ago [5], is the major model used to describe the pathology of AD and other neurodegenerative diseases [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Aβ peptides were synthesized and provided by Dr. Zachary Wills from University of Pittsburgh. High performance liquid chromatography (HPLC), size exclusion chromatography (SEC) and electron microscopy (EM) were used to determine the concentration and oligomeric status of Aβ peptides as described in a recent publication [ 48 ]. Synthesized Aβ42 was dissolved in DMSO and aliquoted before freezing at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…However, synaptic dysfunction by intracellular Aβ occurs long before neurodegeneration in Tg mice. In vitro studies have shown that extracellular Aβ oligomers alter synaptic spine density and morphology and disrupt axonal transport [48][49][50][51][52] and that these toxic effects are mediated by cell surface receptors, such as NMDAR [49,50], an ephrine receptor EphA4 [39], and a Nogo receptor NgR1 [53]. On the other hand, the effects of intracellular Aβ oligomers on synaptic spines and axonal transport were unclear.…”
Section: Cellular Modelsmentioning
confidence: 99%